Lenvatinib Plus Immune Checkpoint Inhibitors Improve Survival in Advanced Hepatocellular Carcinoma: A Retrospective Study - Huang, Xiaozhun; Xu, Lin; Ma, Teng; Yin, Xin; Huang, Zhangkan; Ran, Yihong; Ni, Yong; Bi, Xinyu; Che, Xu (Frontiers in Oncology, 2021)
Background: Nivolumab and pembrolizumab disrupt the programmed cell death-1 immune checkpoint and display promising efficacy and safety results in advanced hepatocellular carcinoma (HCC). However, the benefits remain limited. The preliminary results of lenvatinib (LEN) combined with immune checkpoint inhibitors (ICIs) reveal that the combinations were well-tolerated and encouraging. This study aimed to analyze the safety and efficacy of LEN plus ICIs in a real-world cohort of patients with advanced HCC. Method: Between June 4, 2017, and June 30, 2019, 16 patients received LEN plus nivolumab, and 13 patients were treated with LEN plus pembrolizumab, with the confirmed advanced HCC retrospectively analyzed. The clinical parameters, as well as the outcomes, were assessed. Results: All the patients had Barcelona Clinical Liver Cancer Stage C. LEN with ICIs was used as systemic second-, third-, and fourth-line treatments in seven (24.1%), 14 (48.3%), and eight (27.6%) patients, respectively. At the time of data cutoff, six patients (37.5%) were still receiving LEN with nivolumab, while another six patients (46.2%) were still receiving LEN with pembrolizumab. An objective response was recorded in seven patients (25.9%), while the best overall responses were from one complete response and six partial responses. The 6- and 12-month over survival (OS) rates were 62.6% and 53.7%, respectively. Furthermore, the 6- and 12-month progression-free survival (PFS) rates were 43.5% and 31.8%, respectively. n the subgroup analyses, the 6- and 12-month OS and PFS rates for patients treated with LEN plus nivolumab were 62.5% and 52.1%, respectively, and 43.8% and 30.0%, respectively. The 6- and 12-month OS and PFS rates for patients treated with LEN plus pembrolizumab were 51.3% and 51.3%, respectively, and 49.2% and 49.2%, respectively. A total of 11 (31%) deaths were reported in this study, four of which were attributed to grade 5 adverse events presented as fatal treatment-related hepatitis. Conclusion: The combination of LEN and ICIs is a promising new strategy for the treatment of HCC patients. However, high-grade hepatic toxicity was observed and further evaluation of this combination is still required.